THE ROLE OF SOCIAL MEDIA IN ENHANCING EMPLOYEE AND ORGANIZATIONAL PERFORMANCE THROUGH KNOWLEDGE SHARING, COMMUNICATION, AND DECISION-MAKING - Lutfia, Dinar Dinasty; Permana, Iman (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This study aims to explore the role of social media in improving employee and organizational performance through knowledge sharing, communication, and decision-making. This study was conducted on Bekasi Regency Local Government employees, specifically at the Department of Manpower, with a focus on Generation Z who actively use social media in their daily activities. The research method used is a quantitative approach with a survey as a data collection instrument, which is then analyzed using statistical techniques to test the hypotheses that have been proposed. The study found that knowledge sharing and communication through social media improved employee performance, but had no impact on organizational performance. Meanwhile, decision-making through social media has a positive effect on organizational and employee performance. The limitation of this study is the scope which only covers employees in one particular region, so the results may not be generalizable to other organizational contexts or different generations. Theoretically, this study is expected to make a significant contribution to the literature related to human resource management and information technology. On the practical side, the findings of this research are expected to be a reference for policymakers in formulating a more effective social media utilization strategy in the government work environment.